Calidad seminal pos congelacion en muestra de semen homoespermática y heteroespermática de toros de biotipo pizan - Meza Jama, Dariana Stefania (2024)
The objective of this research was to evaluate sperm quality parameters of cryopreserved straws with homospermatic and heterospermatic semen. The experimental units were made up of 16 cryopreserved straws from 3 bulls of the Pizán biotype, distributed in 4 treatments, homospermatic semen represented by, 4 straws from bull A (T1), 4 straws from Bull B (T2), 4 straws from Bull C (T3). and, finally, 4 T0 straws with heterospermatic semen (mixture of semen from T1, T2 and T3), obtaining a total of 4 treatments and 4 repetitions that constitute the 4 batch or cryopreservation process of the bulls, for the study performed a DBCA design. The variables evaluated were sperm number, motility (total, progressive, circular, fast, slow, local), immotile sperm, mortality, survival analyzed in the CASA system, and total seminal plasma protein by spectrophotometry. The results obtained show that the heterospermatic treatment (T0) presented a lower mortality rate (14.87%), a higher average survival (85.13%) and a higher level of plasma protein (6.58 g/dl), showing significant differences (P <0.05) with respect to treatments T1, T2 and T3; The other microscopic variables did not present statistical differences between the treatments. It is concluded that heterospermatic semen was superior for certain sperm quality parameters, such as mortality, survival and total protein concentration of seminal plasma, however for the rest of sperm quality variables it is similar to homespermatic semen.